Innovative methods for diabetic foot treatment: An integrative review (Research, Society and Development, 2023)
Objective: To investigate innovative and promising treatments for diabetic foot treatment. Methodology: In order to address the guiding question "What are the most modern and available methods for diabetic foot treatment?", an integrative review was conducted by searching for articles in the SciELO, PubMed, and Google Scholar databases, using the descriptors "Diabetes Mellitus," "Diabetic Foot," "Wound Healing," "Therapeutics," "Diabetic foot," "Wound healing," and "Therapy." Inclusion criteria were original articles published from 2017 to 2023 in Portuguese and English. Exclusion criteria encompassed articles unrelated to the study's subject, simple abstracts, book chapters, technical sheets, or experiential reports. Results: 34 articles were included. Among them, those addressing alternative treatments using natural substrates such as medical-grade honey, latex biomembranes, biomembranes with Actinidia deliciosa (kiwi) extract, human placenta and its derivatives were selected. In addition to other diabetic foot wound healing measures, such as ozone therapy, hyperbaric oxygen therapy, ultrasonic irradiation, felt foam, negative pressure wound therapy, topical oxygen, and phototherapy. Conclusion: Through this integrative review, the importance of understanding the different types of treatments used for diabetic foot is highlighted, in order to choose the most appropriate and efficient approach for each case of this chronic complication.